2019
DOI: 10.1038/s41467-019-10779-9
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a 15-stranded actin-like filament from Clostridium botulinum

Abstract: Microfilaments (actin) and microtubules represent the extremes in eukaryotic cytoskeleton cross-sectional dimensions, raising the question of whether filament architectures are limited by protein fold. Here, we report the cryoelectron microscopy structure of a complex filament formed from 15 protofilaments of an actin-like protein. This actin-like ParM is encoded on the large pCBH Clostridium botulinum plasmid. In cross-section, the ~26 nm diameter filament comprises a central helical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…After phosphate release, CBg-ParM remained as a filament without undergoing bulk depolymerization judged by constant light scattering intensity (Fig. 1C), unlike previously studied ParMs (Garner et al ., 2004; Jiang et al ., 2016; Koh et al ., 2019). Supernatant CBg-ParM concentrations in a sedimentation assay indicated that the critical concentrations for polymerization were similar for the different nucleotides, determined to be 2.3 ± 0.1 μM, 2.8 ± 0.1 μM, 1.2 ± 0.1 μM, and 3.6 ± 0.4 μM with ATP, ADP, GTP, and GDP, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After phosphate release, CBg-ParM remained as a filament without undergoing bulk depolymerization judged by constant light scattering intensity (Fig. 1C), unlike previously studied ParMs (Garner et al ., 2004; Jiang et al ., 2016; Koh et al ., 2019). Supernatant CBg-ParM concentrations in a sedimentation assay indicated that the critical concentrations for polymerization were similar for the different nucleotides, determined to be 2.3 ± 0.1 μM, 2.8 ± 0.1 μM, 1.2 ± 0.1 μM, and 3.6 ± 0.4 μM with ATP, ADP, GTP, and GDP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike other ParMs, CBg-ParM did not depolymerize after phosphate release (Fig. 7) (Garner et al ., 2004; Jiang et al ., 2016; Koh et al ., 2019). Instead of depolymerization, the filament underwent a significant structural change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A search of the microbial genomes revealed as many as 40 different families of actin-like proteins, mostly found on plasmids (Derman et al, 2009 ). A few have been shown to assemble into polymeric structures and filaments with varying architectures (Becker et al, 2006 ; Derman et al, 2009 ; Popp et al, 2012 ; Jiang et al, 2016 ; Koh et al, 2019 ). However, the ParMRC system is the most extensively studied among the DNA partitioning systems.…”
Section: Types Of Plasmid Segregation Systemsmentioning
confidence: 99%